Efficacy of Ampelomyces spp. against powdery mildew disease of rose caused by Podosphaera pannosa - N Wanasiri (My University, 2020)
The fungus Ampelomyces spp., a hyperparasite of powdery mildews, was isolated from flowering plants Zinnia elegans, Ageratum conyzoides, Hydrangea sp., and Dahlia spp.The morphological characteristics were observed using light and scanning electron microscopes.Pycnidia variable in shape (ovoid and ellipsoid) and conidia measuring 10.5 to 13.5 µm in length × 2.5 to 3.0 µm in width were detected.Four isolates of Ampelomyces spp.were obtained, AMP1-Ze, AMP2-Ac, AMP3-Hg and AMP4-Dl, to study their ability to inhibit conidial germination on onion cell tissue of the fungus Podosphaera pannosa which causes rose powdery mildew.The biocompounds produced by these mycoparasites had LC50 values between 91.20-190.55 ppm.The most effective biocompound was produced by the Ampelomyces-from Ageratum conyzoides (AMP2-Ac) and it was compared to a conventional fungicide (carbendazim 10cc/20L) and control (non-treated).This biocompound reduced the severity of powdery mildew disease by 45.33% in greenhouse experiments.
Keywords: Rose (mathematics); Fungal disease; Powdery Mildew Fungal Diseases